Pharmacodynamic differences between canagliflozin and dapagliflozin: results of a randomized, double‐blind, crossover study. Issue 2 (5th January 2015) - Sha, S.; Polidori, D.; Farrell, K.; Ghosh, A.; Natarajan, J.; Vaccaro, N.; Pinheiro, J.; Rothenberg, P.; Plum‐Mörschel, L.
<x xml:space="preserve">Abstract</x> Aims To compare the pharmacodynamic effects of the highest approved doses of the sodium glucose co‐transporter 2 (SGLT2) inhibitors canagliflozin and dapagliflozin on urinary glucose excretion (UGE), renal threshold for glucose excretion (RTG) and postprandial plasma glucose (PPG) excursion in healthy participants in a randomized, double‐blind, two‐period crossover study. Methods In each treatment period, participants (n = 54) received canagliflozin 300 mg or dapagliflozin 10 mg for 4 days (20 min before breakfast). A mixed‐meal tolerance test (600 kcal; 75 g glucose) was performed at baseline and on day 4 of each treatment period to assess changes in incremental PPG (PPGΔAUC0–2 h). We measured 24‐h UGE and plasma glucose on day 4 to determine 24‐h mean RTG. Results Canagliflozin 300 mg and dapagliflozin 10 mg had similar effects on UGE and RTG for 4 h after dosing, but canagliflozin was associated with higher UGE and greater RTG reductions for the remainder of the day. Mean 24‐h UGE was ∼25% higher with canagliflozin than with dapagliflozin (51.4 vs. 40.8 g), and 24‐h mean RTG was ∼0.4 mmol/l (7 mg/dl) lower with canagliflozin than with dapagliflozin (3.79 vs. 4.17 mmol/l; p < 0.0001). Dapagliflozin had no effect on PPG excursion; canagliflozin delayed and reduced PPG excursion (between‐treatment difference in PPGΔAUC0–2 h from baseline expressed as a percentage of baseline mean, −10.2%; p = 0.0122). Canagliflozin and dapagliflozin were generally well tolerated. Conclusions In healthy participants, canagliflozin 300 mg provided greater 24‐h UGE, a lower RTG and smaller PPG excursions than dapagliflozin 10 mg.